Alkali metal cation incorporated Ag3BiI6 absorbers for efficient and stable rudorffite solar cells. Issue 1 (20th December 2021) - Wu, Ming-Chung; Kuo, Ruei-Yu; Chang, Yin-Hsuan; Chen, Shih-Hsuan; Ho, Ching-Mei; Su, Wei-Fang
Abstract: Toxic lead and poor stability are the main obstacles of perovskite solar cells. Lead-free silver bismuth iodide (SBI) was first attempted as solar cells photovoltaic materials in 2016. However, the short-circuit current of the SBI rudorffite materials is commonly <10 mA/cm 2, limiting the overall photovoltaic performance. Here, we present a chemical composition engineering to enhance the photovoltaic performance. In this study, we incorporated a series of alkali metal cations (Li +, Na +, K +, Rb + and Cs + ) into Ag3 BiI6 absorbers to investigate the effects on the photovoltaic performance of rudorffite solar cells. Cs + doping improved V OC and Na + doping showed an obvious enhancement in J SC . Therefore, we co-doped Na + and Cs + into SBI (Na/Cs-SBI) as the absorber and investigated the crystal structure, surface morphology and optical properties. The photo-assisted Kelvin probe force microscopy was used to measure surface potential and verified that Na/Cs doping could reduce the electron trapping at the grain boundary and facilitate electron transportation. Na/Cs-SBI reduced the electron–holes pairs recombination and promoted the carrier transport of rudorffite solar cells. Finally, the Na/Cs-SBI rudorffite solar cell not only exhibited a power conversion efficiency (PCE) of 2.50%, a 46% increase to the SBI device (PCE = 1.71%), but also was stable in ambient conditions for >6 months.